Avaliação das curvas de crescimento de equinos da raça Campolina utilizando modelos não lineares - Teixeira, Glaciane Lopes (2020)
The Campolina horse breed has curvilinear features and a well-articulated muscular bone structure, standing out in sports environments such as enduro, traction and leisure. The study of animal growth curves based on non-linear models has often been used as a method for analyzing the development of several species, however, there are no reports of a study on modeling the growth curve in this breed. In this work, the objective was to evaluate the fit of the Logistical, Gompertz, von Bertalanffy and Brody models for the withers height and live weight variables for males and females in data obtained by the transversal method. Higher order derivatives of these growth models were also studied, aiming to identify relevant points of the growth curve such as MAP, IP, MDP and ADP. The experimental data were obtained from an agricultural exhibition in Belo Horizonte / MG, in 2012. A total of 356 animals were measured, 114 males and 242 females of the Campolina breed, which were divided into 16 age classes (7 to 203 months) and sex. The models were compared according to the following criteria for quality of fit: R2, AICC and MAPE. All adjustments, intervals and graphs made were analyzed by the statistical software R. The transversal method of obtaining data can be applied in the study of growth curves, in live weight and withers height for the Campolina breed. The Gompertz model was chosen as the best representative for the animal growth curve in both sexes, as it presents better quality evaluators and captures more influential points from its 1st to 4th order derivatives. The adult withers height value was estimated to be around 160 cm in both sexes and for the variable live weight, 530 kg for females and 494 kg for males. The maturity index of males was higher than that of females, suggesting that the growth of males is more accelerated for withers height. Development in height is more accelerated than in weight, with some important points of growth still occurring in the prenatal phase.